PENGARUH PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN TERHADAP SIKAP KEPEDULIAN SOSIAL - Aulia, Guruh Ryan (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2021)
The National Education of Indonesia has many kind of problems such as the lack of country affection attitude and social concern attitude of the students. This research aims to analyze the effect of civic’s education learning result on social concern attitude toward the 12th grade students of SMA N 4 Medan year 2017 – 2018. This research used quantitative method with the model of double variable relation. The research populations were the all students of 12th grade in SMA N 4 Medan. The samples used in this research consisted of 34 respondents and they were defined based on simple random sampling technique. Based on the research result, it shows that the social concern attitude of 12th grade students in SMA N 4 Medan are in the excellent category for 41, 17 %, good category for 17, 06 % and fair category for 11, 77 %. The effect of civic education learning result on the social concern attitude towards the 12th grade students in SMA N 4 Medan showed the significant effect result. From the calculation, the obtained result was 14,562 of t count value which was bigger than t table, 2,037. It can be concluded that the country affection attitude can be obtained through cognitive aspect, affective aspect, and psychomotor aspect. Moreover, it is also needed to pay full attention to the indirect aspect, for example social media, mass media and electronic media so the shaped positive attitude will not change into negative attitude.